2012
DOI: 10.3109/10929088.2012.668937
|View full text |Cite
|
Sign up to set email alerts
|

Image guided navigation by intraoperative CT scan for cochlear implantation

Abstract: Introduction: For successful cochlear implantation in difficult ears, image guided navigation systems can help identify surgical landmarks or confirm the surgeon's anatomical knowledge. In this pilot case study, exact navigation based on intraoperative CT scanning was investigated and helped confirm important and necessary landmarks, such as the facial nerve, cochlea and intracochlear structures, and at least adequate placement of a straight electrode array. Material and Methods: Intraoperative imaging was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 17 publications
(18 reference statements)
1
25
0
1
Order By: Relevance
“…2). iCT was used for referencing because of its superior accuracy (0.5 mm) (13)(14)(15). Additionally, iCT offered the opportunity to assess the extent of resection during surgery.…”
Section: Mr Imagingmentioning
confidence: 99%
“…2). iCT was used for referencing because of its superior accuracy (0.5 mm) (13)(14)(15). Additionally, iCT offered the opportunity to assess the extent of resection during surgery.…”
Section: Mr Imagingmentioning
confidence: 99%
“…When validated in in vitro accuracy tests, direct navigation system by Jacob et al reported a positioning accuracy of 1.9 mm [12]. A commercial navigation system validated by Stelter et al exhibited spatial deviation of approximately 1 mm in studies involving skull phantoms [13]. In our study, the target registration error was smaller when a portable position sensor was used.…”
Section: Discussionmentioning
confidence: 61%
“…Another direct navigation system, using a mobile-gantry CT scanner, was evaluated in a study by Stelter et al [13]; it used a commercial navigation system that was linked to the CT scanner, was validated using skull phantoms, and was accepted for clinical use in cochlear implantations.…”
Section: Stages Of Workflow In Navigationmentioning
confidence: 99%
“…It gives the surgeon feedback of his performance during cochlear implant surgery. Stelter et al (30) used an intraoperative CT scan for image-guided cochlear implantation. It gives a detailed view of anatomical landmarks in the mastoid.…”
Section: Discussionmentioning
confidence: 99%